An energetic perspective on hydrological cycle changes in the Geoengineering Model Intercomparison Project. Issue 23 (11th December 2013) - Kravitz, Ben; Rasch, Philip J.; Forster, Piers M.; Andrews, Timothy; Cole, Jason N. S.; Irvine, Peter J.; Ji, Duoying; Kristjánsson, Jón Egill; Moore, John C.; Muri, Helene; Niemeier, Ulrike; Robock, Alan; et al.
Abstract [1] Analysis of surface and atmospheric energy budget responses to CO2 and solar forcings can be used to reveal mechanisms of change in the hydrological cycle. We apply this energetic perspective to output from 11 fully coupled atmosphere‐ocean general circulation models simulating experiment G1 of the Geoengineering Model Intercomparison Project (GeoMIP), which achieves top‐of‐atmosphere energy balance between an abrupt quadrupling of CO2 from preindustrial levels (abrupt4xCO2) and uniform solar irradiance reduction. We divide the climate system response into a rapid adjustment, in which climate response is due to adjustment of the atmosphere and land surface on short time scales, and a feedback response, in which the climate response is predominantly due to feedback related to global mean temperature changes. Global mean temperature change is small in G1, so the feedback response is also small. G1 shows a smaller magnitude of land sensible heat flux rapid adjustment than in abrupt4xCO2 and a larger magnitude of latent heat flux adjustment, indicating a greater reduction of evaporation and less land temperature increase than abrupt4xCO2. The sum of surface flux changes in G1 is small, indicating little ocean heat uptake. Using an energetic perspective to assess precipitation changes, abrupt4xCO2 shows decreased mean evaporative moisture flux and increased moisture convergence, particularly over land. However, most changes in precipitation in G1 are in mean evaporative flux, suggesting that changes in mean circulation are small.